Peningkatan Kualitas Produk Paguyuban Jamu Manunggal Kota Cimahi Melalui Standardisasi Bahan Baku - Fahrauk Faramayuda; Ari Sri Windyaswari; Ridwan Ilyas; Dhimas Ariya Wibiksana; Nursafira Khairunnisa Ismail; Reyhan Adriana Deris; Rifaz Muhammad Sukma; Tzazkia Febriyana Akbar; Chandani Nurul Hafizah; Rizka Khoirunnisa Guntina (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
The activity of the community of herbal medicine manunggal in Cimahi city, as the main partner, is to guide the processing of traditional medicines and the herbal medicine business. The proposing team held an initial meeting and socialization for members of the Jamu Manunggal community in the city of Cimahi on December 25, 2021, regarding counseling on planting, post-harvest processing, and the benefits of the cat's whiskers plant. From the results of these activities, several problems were identified: the raw materials for traditional medicines in the Jamu Manunggal Association needed to be better standardized. This activity aims to improve the quality of traditional medicinal products through standardization. The results of the drying shrinkage testing of the five medicinal raw materials met the standards in the Indonesian Herbal Pharmacopoeia. In testing the water-soluble ash content, the levels obtained were not too large illustrating the potential for minor contamination of traditional medicinal raw materials. The general conclusion is that the raw materials for traditional medicine in the Jamu Manunggal Association of Cimahi City have good quality.